PENGARUH MODEL PROBLEM-BASED LEARNING (PBL) BERBASIS TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SEKOLAH DASAR NEGERI PRANAN 01 KECAMATAN POLOKARTO - Mega Utamie, Gebbyella; Anggraeni Siwi, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Problem-Based Learning (PBL) model based on Technological Pedagogical and Content Knowledge (TPACK) on the critical thinking skills of fifth-grade students in IPAS learning. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The subjects were 36 students from SD Negeri Pranan 01 and SD Negeri Pranan 02, Polokarto District. The experimental class consisted of 15 students who learned through PBL based on TPACK, while the control class consisted of 21 students who learned through conventional instruction. Data were collected using a 14-item multiple-choice test and analyzed through the Shapiro-Wilk test, Levene test, and independent samples t-test. The results showed that the experimental class obtained a post-test mean score of 83.40, while the control class obtained 54.08. The t-test significance value was 0.000 < 0.05. Therefore, PBL based on TPACK had a significant effect on students critical thinking skills.